The Oblique Incidence of the Flat Wave on the Wall with Metallic Lattice Inside - Ziemelis, J.; Solovjova, T. (Elektronika ir Elektrotechnika, 2006)
This paper contains findings of authors, which concern reflection and transmission electromagnetic waves in case of oblique incidence for dielectric slab with metallic lattice with periodic structure inside. The reflected and transmitted fields are calculated by solving boundary problem. For solving periodic structure field decomposition in TE and TM wave types is applied. The highest modes create near surface of the wall the complicated field distribution and cross polarization. Such field distribution does not permit model without periodic structure inside. Only if geometry structure and wavelength of incident wave allow not arising propagative highest modes, a possibility to create easy mathematical model for far zone observation point exists. Ill. 7, bibl. 4 (in English; summaries in English, Russian and Lithuanian).